Application of anaerobic digestion model no 1 in biohydrogen optimization using palm oil mill effluent: effect of pretreatment method - Ahmad Zul Izzi Fauzi (2023)
Biohydrogen is an environmentally friendly and sustainable alternative energy carrier to fossil fuels. However, low yield and inconsistent processes have hindered its large-scale production. This research aims to address these challenges by increasing the reduced sugar (RS) content of Palm Oil Mill Effluent (POME), enhancing biohydrogen yield in subsequent fermentation processes, developing a process model, and determining the dominant microbial species in the effluent. The work is divided into four main parts. The first part examines the effects of pretreatment on RS yield using acid, alkaline, and enzymatic methods. The second part focuses on biohydrogen production under thermophilic conditions using the pretreated POME as a substrate and digested sludge as inoculum. The optimization of both parts is achieved using Box-Behnken Design in a batch process. In the third part, kinetic modelling uses the modified Anaerobic Digestion Model No. 1 (ADM1) to describe the biochemical and physicochemical processes by fitting experimental data on hydrogen evolution, RS degradation, and volatile fatty acid (VFA) formation. Finally, the fourth part involves screening the dominant microbial community responsible for biohydrogen conversion using 16S rDNA sequencing methods. Results indicate that the pretreatment method improved RS recovery from acid, alkaline, and enzymatic pretreatment by 13%, 9.35%, and 182%, respectively. Optimization of the biohydrogen production process at a temperature of 55°C, mixing speed of 150 rpm, chemical oxygen demand (COD) concentration of 39,706 mg/L, seed content of 13.64%, and an initial pH of 6 significantly increased the biohydrogen production potential (Hmax) by five-fold (444 mL). The ADM1-based model shows a good fit for all models (hydrogen evolution, RS degradation, and VFA formation) with a high R2 above 0.94 and a small standard error of ≤ 0.2. The models were highly significant, with P-values far less than 0.05. Furthermore, the taxonomic analysis revealed that Thermoanaerobacterium thermosaccharolyticum species was the predominant hydrogenproducing bacterium among the diverse microbial genera. These findings provide a good basis for the further development of biohydrogen production from POME. The proposed process design, optimization, and control could lead to direct implementation in a largescale plant.